Micro Mineral Concentration in Soil, Plant and Dairy Cattle in Andaman Group of Islands - Hegde, M. Sujata; ., Jaisunder; Kumaresan, A.; Datt, Chander; Singh, Pawan; Singh, Avtar (Indian Journal of Animal Nutrition, 2018)
The present work was undertaken with the aim to estimate minerals status in soil, composite plant samples and dairy cattle in six blocks viz., Prothrapur, Ferrargunj, Little Andaman, Diglipur, Rangat and Mayabunder of Andaman group of islands. A total of 102 samples each of soil, composite plant and cattle bloodserum were taken randomly from each block. All the samples were analysed for estimation of micro minerals (Zn, Fe, Mn, Cu and Co). The results revealed that the overall mean concentration of Zn (1.25±0.27 ppm), Fe (76.02±10.54 ppm), Mn (37.66±5.04 ppm) and Cu (1.61±0.32 ppm) in soil was higher than the critical level and differed significantly (P